The Protein Corona Leads to Deformation of Spherical Micelles. Issue 18 (23rd March 2021) - Cao, Cheng; Zhang, Lin; Kent, Ben; Wong, Sandy; Garvey, Christopher J.; Stenzel, Martina H.
Abstract: The formation of a non‐specific protein corona around nanoparticles (NPs) has been identified as one of the culprits for failed nanomedicine. The amount and type of adsorbed protein from the blood plasma are known to determine the fate of NPs and the accessibility of targeting ligands. Herein, we show that the adsorbed protein may not only enlarge the NPs and change their surface properties but also, in the case of soft NPs such as polymer micelles, lead to deformation. Poly(1‐ O ‐methacryloyl ‐β‐D‐fructopyranose)‐ b ‐poly(methylmethacrylate) (P(1‐ O ‐MAFru)‐ b ‐PMMA) block co‐polymers were self‐assembled into NPs with a spherical core–shell morphology as determined by small angle neutron scattering (SANS). Upon incubation with albumin, TEM, SANS, and small angle X‐ray scattering (SAXS) revealed the adsorption of albumin and deformation of the NPs with a spheroid geometry. Removal of the protein led to the reversal of the morphology back to the spherical core–shell structure. Structural studies and cell studies of uptake of the NPs imply that the observed deformation may influence blood circulation time and cell uptake. Abstract : A fructose‐based block copolymer was self‐assembled into four different micelles with various shell polymer densities. The most brush‐like micelle was observed to have the highest amount of protein adsorption and the lowest cellular uptake. Small angle scattering revealed that the protein corona transformed the spherical micelles into spheroidal micelles and the nanoparticles used in the biological experiment were therefore non‐spherical.